Pelatihan Kewirausahaan Dalam Mengelola Bahan Limbah Batok Kelapa Menjadi Lampu Hias, Lonceng Dan Asbak Di SMA Negeri 2 Percut Sei Tuan - Pinondang Hutapea; Melda Panjaitan (Cattleya Darmaya Fortuna, 2026)
This community service program aims to improve the basic competency of students at Senior High School Negeri 2 Percut Sei Tuan in utilizing coconut shell waste to enhance their creativity and the community's economic well-being. In the digital era, students are required not only to master learning theory but also to demonstrate their creativity in utilizing coconut shell waste. This will enable them to create businesses and market their products using social media, thereby contributing to the growth of the community's economy. The program's methodology includes coordination with the principal, literacy workshops, and training on utilizing coconut shell waste, which can be directly demonstrated by students at school. This training is conducted by students in groups with hands-on practice, supervised, and evaluated. The program is designed to involve students at Senior High School Negeri 2 Percut Sei Tuan as the primary participants. The expected outcomes of this program are increased student creativity in utilizing coconut shell waste, entrepreneurial skills, and marketing skills through social media. Thus, this activity is expected to support economic growth and reduce coconut shell waste.